Meretas Filsafat Pendidikan Materialisme-Naturalisme dalam Konteks Pendidikan Dasar - Hestia Alika K; Jessica Andriany; Selvi Oktavia; Resa Agustina; Ayut Nursusanti; Arita Wahyuni (Program Studi PGSD Universitas Madako Tolitoli, 2023)
It investigates the extent to which previous researchers in the context of Indonesian writers have talked about the philosophy of (educational) naturalism and the philosophy of materialism, especially when confronted with Basic/Elementary Education. Researchers see that there are still few who write about the relationship between these two philosophies and Basic Education. In fact, Basic Education in Indonesia has become an education program. This research method is a literature review by searching for sources from recent journals. The results show that the relationship between the philosophies of naturalism and materialism is so close, it is even difficult to find the extent of the gap between the two philosophies in relation to the world of education, especially in the context of Basic Education.